INDONESIAN SHARIA BANK, A PROGRESS OR PACKAGE FOR INDONESIAN SHARIA BANKING - Pratiwi, Annisa Ghea; Fabian, Vincentius; Nugraha, Yudi; Suhadharatan, Raden Maulana; Nuraeni, Reni; Wijaya, John Henry (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to determine whether the merger of Himbara Syariah Banks consisting of BRI Syariah Banks, BNI Syariah Banks and Mandiri Syariah Banks can improve the performance of the Islamic banking sector in general and in particular to determine the performance of the bank resulting from the merger, namely Bank Syariah Indonesia. The research method used is by using an unpaired difference test, namely the Mann Whitney test, with a comparison between before and after combining for 182 days each. The results showed that it turned out that the merger had a fairly good impact on the performance of the Islamic bank, although it had only been running for 182 days. advancing the world of Islamic banking in Indonesia can run well and smoothly.